Survival, oxidative stability, and surface characteristics of spray dried co-microcapsules containing omega-3 fatty acids and probiotic bacteria. Issue 16 (9th December 2016) - Eratte, Divya; Gengenbach, Thomas R.; Dowling, Kim; Barrow, Colin J.; Adhikari, Benu
ABSTRACT: The objective of the study was to determine optimum inlet and outlet air temperatures of spray process for producing co-microcapsules containing omega-3 rich tuna oil and probiotic bacteria L. casei . These co-microcapsules were produced using whey protein isolate and gum Arabic complex coacervates as shell materials. Improved bacterial viability and oxidative stability of omega-3 oil were used as two main criteria of this study. Three sets of inlet (130°C, 150°C, and 170°C) and outlet (55°C, 65°C, and 75°C) air temperatures were used in nine combinations to produce powdered co-microcapsule. The viability of L. casei, oxidative stability of omega-3 oil, surface oil, oil microencapsulation efficiency, moisture content, surface elemental composition and morphology of the powdered samples were measured. There is no statistical difference in oxidative stability at two lower inlet air temperatures (130°C and 150°C). However, there was a significant decrease in oxidative stability when higher inlet temperature (170°C) was used. The viability of L. casei decreased with the increase in the inlet and outlet air temperatures. There was no difference in the surface elemental compositions and surface morphology of powdered co-microcapsules produced under these nine inlet/outlet temperature combinations. Of the range of conditions tested the co-microcapsules produced at inlet-outlet temperature 130–65°C showed the highest bacterial viability and oxidative stability of omega-3 and having the moisture content of 4.93 ± 0.05% (w/w). This research shows that powdered co-microcapsules of probiotic bacteria and omega-3 fatty acids with high survival of the former and high stability against oxidation can be produced through spray drying.